PENGARUH PENDEKATAN PROBLEM-BASED LEARNING BERSTRATEGI ACT IT OUT TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN MOTIVASI BELAJAR SISWA - Maharani, Wintari; Irawati, Riana; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
The purpose of this research are to know about the influence of PBL with Act It Out strategy to the mathematical understanding ability and learning motivation of students. Quasi experimental is a method that used, with nonequivalent control group design. The students of class IV SDN Majalengka Kulon V as an experimental, and SDN Majalengka Wetan III as a control class are the samples. Based on data analysis, it’s proven that PBL with Act It Out strategy could improve the mathematical understanding ability better than conventional learning with significantly, and could improve the learning motivation of student with insignificantly. A positive correlation between those aspects indicates that student who have a high of mathematical understanding ability shown have a high of learning motivation too. The students respons to that approach generally positive, based on they answers from interview.